Conductive-probe atomic force microscopy as a characterization tool for nanowire-based solar cells. (November 2017) - Mikulik, Dmitry; Ricci, Maria; Tutuncuoglu, Gozde; Matteini, Federico; Vukajlovic, Jelena; Vulic, Natasa; Alarcon-Llado, Esther; Fontcuberta i Morral, Anna
Abstract: The photonic properties of nanowires advocate for their utilization in next generation solar cells. Compared to traditional devices, the electric scheme is transformed from a single into an ensemble of pn junctions connected in parallel. This new configuration requires new schemes for the characterization. We show how conductive-probe atomic force microscopy, C-AFM, is an essential tool for the characterization and optimization of this parallel-connected nanowire devices. With C-AFM it is possible to obtain both surface topography and local electrical characterization with nanoscale resolution. We demonstrate topography and current mapping of nanowire forests, combined with current-voltage measurements of the individual nanowire junctions from the ensemble. Our results provide discussion elements on some factors limiting the performance of a nanowire-based solar cell and thereby to provide a path for their improvement. Graphical abstract: Highlights: Conductive atomic force microscopy is applied to nanowire-based solar cells. The statistical properties of the nanowire pn-junctions is studied. The performance of single nanowire devices is compared to the full device. Non-uniformity of electrical properties in the nanowire ensemble is revealed. A few poor-performing nanowire devices may not be critical for the full device.